A Semi-Analytical Method for Nonlinear System of Delay Differential Equation via Modified He’s Polynomial - Yohanna Nehemiah; Aminu Barde; A. Madaki; Michael Cornelius (Darul Yasin Al Sys, 2025)
In this work, a simple technique based on the combination of sumudu transform and variational iteration method via Modified He’s polynomial is introduced to solve systems of non-linear delay differential equations. The introduced technique is simpler and shorter in its computational procedures and time than the other methods. In addition, the modified He’s polynomial takes care of the nonlinear terms and hence, making the method less stressful in terms of computations. Also, this technique reduces the complexity of calculating Lagrange’s multiplier values which need more computational procedures and time. These advantages make it reliable and its efficiency is demonstrated with numerical examples.